Combined scheduling algorithm for re-entrant batch-processing machines in semiconductor wafer manufacturing - Jia, Wenyou; Jiang, Zhibin; Li, You (International journal of production research, 2015)
In this paper, a new combined scheduling algorithm is proposed to address the problem of minimising total weighted tardiness on re-entrant batch-processing machines (RBPMs) with incompatible job families in the semiconductor wafer fabrication system (SWFS). The general combined scheduling algorithm forms batches according to parameters from the real-time scheduling simulation platform (ReS 2 ), and then sequences batches through slack-based mixed integer linear programming model (S-MILP), which is defined as batch-oriented combined scheduling algorithm. The new combined scheduling algorithm obtains families' parameters from ReS 2 and then sequences these families through modified S-MILP, which is defined as family-oriented combined scheduling algorithm. With rolling horizon control strategy, two combined scheduling algorithms can update RBPMs scheduling continually. The experiments are implemented on ReS 2 of SWFS and ILOG CPLEX, respectively. The results demonstrate the effectiveness of our proposed methods.